Systematic Literature Review on the Effects of City Branding Balikpapan on Tourism Interest and Consumer Behavior - Irfan Taufik; Sudarmiatin Sudarmiatin; Agus Hermawan (Harmony Management: International Journal of Management Science and Business, 2025)
This study conducts a Systematic Literature Review (SLR) of 20 empirical and conceptual articles published between 2020 and 2025 to examine the influence of city branding on tourism interest and consumer behavior, with a particular focus on the city of Balikpapan. The synthesis reveals that city branding significantly shapes tourist perceptions through key elements such as destination image, brand identity, brand personality, and digital communication. Destination image consistently emerges as the primary mediator linking city branding to visit intention, while experiential and emotional branding further strengthen tourists’ cognitive, affective, and behavioral responses. The findings also highlight the growing importance of digital media and e-WOM in amplifying city branding strategies, especially in the post-pandemic tourism landscape. Despite strong branding potential rooted in cleanliness, safety, and Balikpapan’s strategic role as a supporting city for the new capital (IKN), gaps remain in digital branding, differentiation, and identity storytelling. The review emphasizes the need for more integrated, innovative, and data-driven branding approaches to enhance the city’s competitiveness and attract greater tourism engagement.